Developments of mucus penetrating nanoparticles - Min Liu; Jian Zhang; Wei Shan; Yuan Huang (Elsevier, 2015)
Mucus can effectively protect the exposed mucosal surfaces due to its adhesive and viscoelastic properties. Most foreign particulates are efficiently trapped in mucus layers via steric obstruction and adhesion. Trapped particles are typically removed from the mucosal tissue within seconds to a few hours depending on their location sites. This article focuses on describing the tenacious mucus barrier properties, the strategies to investigate the interaction of nanoparticles with the mucus as well as the novel developments of mucus penetrating nanoparticles.